A EFEKTIVITAS PENGGUNAAN LEMBAR KERJA PESERTA DIDIK DENGAN PENDEKATAN PEMECAHAN MASALAH TERHADAP KETRAMPILAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN MATEMATIKA MATERI BANGUN DATAR KELAS V SEKOLAH NEGERI 01 SIDOMUKTI KECAMATAN JENAWI TAHUN AJARAN 2023/2024 - Undari, Amelia Putri; Sari, Nurratri Kurnia; Sutrisno, Tri (EJOIN : Jurnal Pengabdian Masyarakat, 2023)
The aim of this research is: to find out whether there is effectiveness in using student worksheets with a problem solving approach on students' critical thinking skills in the mathematics subject of plane figures for class V State Elementary School 01 Sidomukti, Jenawi District, Academic Year 2023/2024. This research uses a comparative descriptive method. The subjects in this research were 20 fifth grade students at SD Negeri 01 Sidomukti. The research design used was one design pretest and posttest group. The data collection techniques used are documentation and tests in the form of pretest and posttest. Data analysis techniques include normality test and t test. The research results showed that the students' average score on the pretest was 60.50 and on the posttest it was 78.85. This shows that there is a change in the mean during the pre-test and post-test. The results of the t test obtained a two tailed value of 0.000 < significant value (alpha: 0.05) so that it falls in the area of ​​rejection of Ho and acceptance of Ha. Therefore, the t test states that there is effectiveness in using student worksheets in the mathematics subject material on flat shapes for class V at SD Negeri 01 Sidomukti, Jenawi District, Academic Year 2023/2024